2015
DOI: 10.1086/680357
|View full text |Cite
|
Sign up to set email alerts
|

A Nonmuscle Myosin Light Chain Kinase–Dependent Gene Signature in Peripheral Blood Mononuclear Cells is Linked to Human Asthma Severity and Exacerbation Status

Abstract: ; a TW and JGNG contributed equally as senior authors.Abstract: Asthma is increasingly recognized as a heterogeneous disease influenced by complex genetic and environmental contributions. Myosin light chain kinase (MLCK; gene symbol, MYLK ), especially the nonmuscle isoform nmMLCK, is a cytoskeleton protein known to be related to human asthma susceptibility and severity, findings confirmed in preclinical models of asthmatic inflammation. In this study, we define the central capacity for a nmMLCK-influenced gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Numerous cell activities, such as contraction, adhesion, cell migration, and epithelial barrier formation occur in a myosin regulatory light chain (MLC) phosphorylation dependent or independent manner ( Chen et al, 2013 ; Chen C. et al, 2014 ; Kim and Helfman, 2016 ). Abnormal expression of MLCK has been observed in many inflammatory diseases including pancreatitis ( Shi et al, 2014 ), respiratory diseases ( Zhou et al, 2015 ), cardiovascular diseases ( Cheng et al, 2015 ), cancer ( Zhou et al, 2014 ), and inflammatory bowel disease (IBD) ( Yi et al, 2014 ). The involvement of MLCK and the MLCK signaling pathway that underlie representative inflammatory diseases is discussed.…”
mentioning
confidence: 99%
“…Numerous cell activities, such as contraction, adhesion, cell migration, and epithelial barrier formation occur in a myosin regulatory light chain (MLC) phosphorylation dependent or independent manner ( Chen et al, 2013 ; Chen C. et al, 2014 ; Kim and Helfman, 2016 ). Abnormal expression of MLCK has been observed in many inflammatory diseases including pancreatitis ( Shi et al, 2014 ), respiratory diseases ( Zhou et al, 2015 ), cardiovascular diseases ( Cheng et al, 2015 ), cancer ( Zhou et al, 2014 ), and inflammatory bowel disease (IBD) ( Yi et al, 2014 ). The involvement of MLCK and the MLCK signaling pathway that underlie representative inflammatory diseases is discussed.…”
mentioning
confidence: 99%
“…Previous studies indicated that MLCK is involved in a variety of T-cell immune responses in various diseases and has a central role in asthmatic inflammation. The level of MLCK was reported to be correlated with the severity and susceptibility to asthma ( 15 ). The results of the present study demonstrated that ML-7 inhibited airway inflammation and remodeling in an OVA-induced mouse model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MLCK regulates numerous biological functions through up-regulation of NADPH oxidase, tumor necrosis factor receptor 2 signaling and notch signaling ( 13 , 14 ). The signaling effect of MLCK in chronic asthma has been reported by several studies, including the regulation of the inflammatory response and vascular permeability ( 15 ). The mechanism of MLCK in smooth muscle cells and the immune regulation of T cells is complex, inducing a variety of cytokines in the occurrence and development of disease ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 97%
“…There are multiple MLCK proteins, but the focus of the present study is a 210-kDa MLCK protein encoded by the mylk1 genetic locus, referred to as MLCK210 (for review see Khapchaev and Shirinsky 2016). Prior studies on the role of MLCK210 in tissue barrier dysfunction and the potential of selective inhibitors have largely focused on non-CNS disorders (for recent reviews see Cunningham and Turner 2012; Rigor et al 2013; Khapchaev and Shirinsky 2016; Xiong et al 2017), including acute lung injury models (Wainwright et al 2003; Rossi et al 2007; Mirzapoiazova et al 2011; Usatyuk et al 2012; Fazal et al 2013; Wang et al 2014; Wang et al 2016; Zhou et al 2015), burn injury (Reynoso et al 2007; Guo et al 2012; Zahs et al 2012), acute diarrhea (Clayburgh et al 2005; Clayburgh et al 2006), endotoxic shock (Ralay Ranaivo et al 2007; Gaceb et al 2016), cardiovascular shear stress (Ohlmann et al 2005), atherosclerosis (Sun et al 2011), hypoxia (Arnaud et al 2018), and intestinal injury models (Al-Sadi et al 2012; Gilbert et al 2012; Wu et al 2014; Lorentz et al 2017; Nighot et al 2017; Al-Sadi et al 2019). Additionally, there exists a smaller literature exploring the benefit of inhibition of MLCK in the context of BBB dysfunction.…”
Section: Introductionmentioning
confidence: 99%